The Constant in this expression 5x+10 is 10.
A mathematical operation such as subtraction, addition, multiplication, or division is used to combine terms into an expression. In a mathematical expression, the following terms are used:
Given:
Expression: 5x+10
The terms in an expression is 5x and 10.
As, the constant is the number whose value does not change in remain constant and is withoutvariable.
Thus, the constant is 10.
Learn more about Expression here:
#SPJ6
The constant in this equation is 10
A constant in an equation is a number that is on its own, or without a variable.
5x would not be a constant because they are not alone.
10 is the stand-alone number in this equation, therefore, 10 is the constant.
Answer:
1.225km is equal to each laps
Step-by-step explanation:
Since Kristy total distance traveled = 29.6km
And Kristy ran 24 laps and later walk 0.2km. it simply implies that
Total distance traveled = distance covered running + distance covered walking
Since we know that
Total distance traveled = 29.6km
distance covered running = 24 laps
distance covered walking = 0.2km
Distance covered running in km = total distance traveled - distance covered walking
Distance covered running in km = 29.6km - 0.2km = 29.4km.
To now find the distance for each lap.
Since we have:
Distance covered running in km = 29.4km.
Distance covered running in lap = 24 laps
i.e
24 laps = 29.4km
1 lap = x
Use cross-multiple
24 laps * x = 29.4km × 1 lap
x = 29.4km / 24
x = 1.225km
Therefore
1.225km is equal to each laps.
totaldistanceof24laps
29.6km - 0.2km
=29.4km
totaldistanceofeachlap
24 laps = 29.4km
1 lap = ?
Usecross-multiple
24 laps × X = 29.4km × 1 lap
X = 29.4km / 24
X = 1.225km
Answer
1.225km
The resultant of the given expression 9(3+c+4) using distributive property will be 63 + 9c.
A mixture of variables, numbers, addition, subtraction, multiplication, and division are called expressions.
A statement expressing the equality of two mathematical expressions is known as an equation.
As per the given expression,
9(3+c+4)
⇒ 9(7+c)
By using distribution property,
⇒ 9(7)+9c
⇒63+9c
Hence "The resultant of the given expression 9(3+c+4) using distributive property will be 63 + 9c".
To learn more about expression,
#SPJ2
9(3+c+4)
9(7+c)
9(7)+9c
Answer:
63+9c